2017 IEEE 4th International Conference on Cyber Security and Cloud Computing (CSCloud) 2017
DOI: 10.1109/cscloud.2017.15
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning for Anomaly Detection and Categorization in Multi-Cloud Environments

Abstract: Cloud computing has been widely adopted by application service providers (ASPs) and enterprises to reduce both capital expenditures (CAPEX) and operational expenditures (OPEX). Applications and services previously running on private data centers are now being migrated to private or public clouds. Since most of the ASPs and enterprises have globally distributed user bases, their services need to be distributed across multiple clouds, spread across the globe which can achieve better performance in terms of laten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 22 publications
0
54
0
1
Order By: Relevance
“…As shown in Table 5, our dataset is unbalanced. Therefore, accuracy is not the ideal measure to evaluate the performance [33]. Other metrics are needed to compare the performance of the ML algorithms.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…As shown in Table 5, our dataset is unbalanced. Therefore, accuracy is not the ideal measure to evaluate the performance [33]. Other metrics are needed to compare the performance of the ML algorithms.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…A. Our Preliminary work: In our preliminary work [41,46], we have demonstrated that machine learning techniques need significant rework to perform satisfactorily in the context of anomaly detection in ICSs. The major challenge in the application of machine learning methods is obtaining real-time and unbiased datasets.…”
Section: Research Challengesmentioning
confidence: 99%
“…The authors in [12] performed random forest binary classification on various stages to classify eight kinds of attacks. They compared logistic regression and random forest for anomaly detection and showed that RF outperformed LR.…”
Section: Related Workmentioning
confidence: 99%